Risk Constructs Behind Ontario Domestic Assault Risk Assessment - Pham, Anna T. (Victims & offenders, 2024)
Actuarial risk assessment measures are often criticized because items are typically historical and do not capture potential change. Latent variable models are used to link historical risk factors to risk domains that may be the target of intervention. Using exploratory factor analysis, we explored the latent factors of the Ontario Domestic Assault Risk Assessment (ODARA) and the extent to which factors predict general, any violent, and IPV recidivism by conducting area under the receiver operating characteristic curve (AUC). We found that the ODARA contains three factors, which could be best attributed as antisocial patterns, victim vulnerabilities, and index offense-related. Antisocial Patterns significantly predicted all outcomes, whereas Victim Vulnerabilities only predicted general reoffending, and Index Offense did not reliably predict any of the recidivism outcomes. Moreover, Antisocial Patterns predicted all recidivism outcomes as well as the ODARA total. Additionally, Antisocial Patterns was able to predict any violent and general reoffending significantly better than Victim Vulnerabilities and Index Offense. Given that only Antisocial Patterns could predict IPV recidivism, our current understanding of factors unique to IPV needs further exploration to increase understanding and conceptualization of factors most strongly associated with IPV offenses, thereby improving the assessment of risk.